Performance Of Micro Gas Turbine Combustion Chamber With Diesel Fuel - Nudin, Saparuddin (Universiti Sains Malaysia, 2017)
Development of micro gas turbine has increased in recent year due to high reliability and the ability of self-generating. MGT system also provides lower power losses and it can operate on both renewable and non-renewable fuels with low level of gas emission. However, without right design of combustion chamber, sufficient amount air and better spray characteristic of liquid fuel will causes incomplete combustion occurred and lead to high level of gas emissions. In this paper, a MGT system was developed by using a Garret turbocharger GT25 with a combustion chamber to operate with diesel fuel. A spraying characteristic was studied of diesel fuels using various nozzles. The MGT system was characterized experimentally with liquefied petroleum gas (LPG) for warm up session and diesel fuel for full operation. The MGT system has achieved low level of CO and NOx emission of about 95ppm and 31ppm respectively. Besides that, design of dilution zone at the combustion chamber able to prevent temperature of gas exhaust exceeding 1000oC.